La France en Polynésie française : quelle volonté de rester présente ? - Jean-Marc Regnault (EchoGéo)
Does France have a long-term plan for it’s Overseas Territories, and for French Polynesia in particular ? Or is such a plan emerging gradually under the pressure of reality ? Right now, rather opposing signals are being sent by the Central Government’s attitude. With a French President who wants a clear change from his predecessor’s policies, a disengagement seems obvious, but, institutionally, it yet has to be defined which is the best way for France to continue to « shine » in Oceania. What is certain - despite contradictory speeches - is that the financial windfall that used to irrigate French Polynesia will decrease and that controls on the spending of Government subsidies will multiply. Will there ultimately be a « less central Government for better central Government »?